Is ovarian recovery after chemotherapy in young patients with early breast cancer influenced by controlled ovarian hyperstimulation for fertility preservation or tumor characteristics? Results of a prospective study in 126 patients. Issue 11 (7th February 2022) - Mailliez, Audrey; Pigny, Pascal; Bogart, Emilie; Keller, Laura; D'Orazio, Emmanuelle; Vanseymortier, Marie; Le Deley, Marie‐Cécile; Decanter, Christine
Abstract: Young individuals, aged <40 years, represent 7% of all patients with early breast cancer (EBC), most of whom receive chemotherapy. Preserving future fertility in these patients has become a major concern. This prospective study assessed ovarian function during and after chemotherapy according to patient and tumor characteristics and evaluated the outcome of controlled ovarian hyperstimulation (COH). Ovarian reserve was evaluated in terms of amenorrhea duration and by longitudinal serum anti‐Müllerian hormone (AMH) level variations measured at study entry, during treatment and until 24 months thereafter. COH has been proposed for patients receiving adjuvant chemotherapy. We studied the association between clinical factors and ovarian function using Cox models and logistic regression. In this young population (age < 38 years, median = 32), 85 of 90 evaluable patients (94%) experienced chemo‐induced amenorrhea, including six persistent amenorrhea and one chemotherapy‐induced definitive ovarian failure. Overall, 33% of patients still had undetectable AMH values 12 months after the end of chemotherapy, although most had recovered spontaneous and regular menstrual function. No specific factor was associated with clinical or biological late ovarian dysfunction, except for age and baseline AMH value. Overall, 58 patients underwent COH. The mean number of total retrieved oocytes and metaphase II oocytes were of 11.7 and 6.9, respectively. Thus, our study confirms the importance of fertility preservation in young patients with EBC. Our findings indicate that sequential chemotherapy is associated with a higher risk of persistent amenorrhea. There was no significant association between tumor characteristics, fertility preservation or recovery of ovarian reserve. Abstract : What's new? Serum anti‐Müllerian hormone (AMH) is a marker of ovarian follicular content and a real‐time indicator of both follicular depletion and ovarian recovery in patients with cancer. This prospective study describes the menstrual function and dynamics of serum AMH variations during and after chemotherapy in premenopausal patients treated for breast cancer. The findings indicate that sequential chemotherapy is associated with a higher risk of persistent amenorrhea. There was no significant association between tumor characteristics, fertility preservation with controlled ovarian hyperstimulation or recovery of the ovarian reserve. The study underlines the necessity of fertility preservation before commencing chemotherapy.